“Incidente na raiz” e “operação pente fino”: A discussão sobre o racismo em obras de cuti - Silva, Célio Pereira (Universidade Federal do Tocantins, 2022)
This work proposes to analyze works by the writer Luiz Silva (Cuti), in view of the denunciation of the racism present in them. The research makes a brief reflection on the panorama history of how the figure of the black was delineated in our canonical literature, in which, general, the black person was personified permeated by prejudices and stigmas. So is It is very important to research writers like Cuti, because in our In literature, the voice heard has always been that of the privileged subject, who, far from other identities, speaks of them from the ideology of their place of speech. Cuti, who recognizes himself as a black subject, attributes humanity to its characters, criticizes and denounces racism. The works analyzed are the short story Incidente na Raiz and the poem Operação pente fino, in which the author denounces all oppression under the black subject's body.